Instability Mechanism of Osimertinib in Plasma and a Solving Strategy in the Pharmacokinetics Study - Yuan, Zheng; Yu, Xin; Wu, Siyang; Wu, Xiaonan; Wang, Qiutao; Cheng, Wenhao; Hu, Weiyu; Kang, Chen; Yang, Wei; Li, Yingfei; Zhou, Xiao-Yang (Frontiers in Pharmacology, 2022)
Osimertinib is a third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) and a star medication used to treat non-small-cell lung carcinomas (NSCLC). It has caused broad public concern that osimertinib has relatively low stability in plasma. We explored why osimertinib and its primary metabolites AZ-5104 and AZ-7550 are unstable in rat plasma. Our results suggested that it is the main reason inducing their unstable phenomenon that the Michael addition reaction was putatively produced between the Michael acceptor of osimertinib and the cysteine in the plasma matrix. Consequently, we identified a method to stabilize osimertinib and its metabolites contents in plasma. The assay was observed to enhance the stability of osimertinib, AZ-5104 and AZ-7550 significantly. The validated method was subsequently applied to perform the pharmacokinetic study for osimertinib in rats with the newly established, elegant, and optimized ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS) strategy. The assay was assessed for accuracy, precision, matrix effects, recovery, and stability. This study can help understand the pharmacological effects of osimertinib and promote a solution for the similar problem of other Michael acceptor-contained third-generation EGFR-TKI.